Molecular hydrogen in the extremely metal- and dust-poor galaxy Leo P - Telford, Grace; Sandstrom, Karin M.; McQuinn, Kristen B. W.; Glover, Simon; Tarantino, Elizabeth J.; Bolatto, Alberto D.; Rickards Vaught, Ryan J. (Nature, 2025)
The James Webb Space Telescope (JWST) has revealed unexpectedly rapid galaxy assembly in the early Universe, in tension with galaxy-formation models1-3. At the low abundances of heavy elements (metals) and dust typical in early galaxies, the formation of molecular hydrogen and its connection to star formation remain poorly understood. Some models predict that stars form in predominantly atomic gas at low metallicity4,5, in contrast to molecular gas at higher metallicities6. Despite repeated searches7, cold molecular gas has not yet been observed in any galaxy below 7% solar metallicity8. Here we report the detection of rotational emission from molecular hydrogen near the only O-type star in the 3% solar metallicity galaxy Leo P (refs. 9,10) with JWST’s Mid-Infrared Instrument/Medium Resolution Spectroscopy (MIRI-MRS) observing mode. These observations place a lower limit on Leo P’s molecular gas content, and modelling of the photodissociation region illuminated by the O star suggests a compact (≤2.6 pc radius), approximately 104 M⊙ cloud. We also report a stringent upper limit on carbon monoxide (CO) emission from a deep search with the Atacama Large Millimeter/submillimeter Array (ALMA). Our results highlight the power of MIRI-MRS to characterize even small ultraviolet-illuminated molecular clouds in the low-metallicity regime, in which the traditional observational tracer CO is uninformative. This discovery pushes the limiting metallicity at which molecular gas is present in detectable quantities more than a factor of two lower, providing crucial empirical guidance for models of the interstellar medium in early galaxies.